2017
DOI: 10.1038/npp.2017.155
|View full text |Cite
|
Sign up to set email alerts
|

Antimanic Efficacy of a Novel Kv3 Potassium Channel Modulator

Abstract: Kv3.1 and Kv3.2 voltage-gated potassium channels are expressed on parvalbumin-positive GABAergic interneurons in corticolimbic brain regions and contribute to high-frequency neural firing. The channels are also expressed on GABAergic neurons of the basal ganglia, substantia nigra, and ventral tegmental area (VTA) where they regulate firing patterns critical for movement control, reward, and motivation. Modulation of Kv3.1 and Kv3.2 channels may therefore have potential in the treatment of disorders in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…The main conclusion currently is that KO females have the lowest anxiety-like behavior and appear resilient to the anxiogenic effects of chronic stress. Low anxiety in Kv3.1 KOs has previously been reported in males (Parekh et al, 2018); these results replicate this observation in females. This study is the first to combine Kv3.1 deficiency with chronic stress.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The main conclusion currently is that KO females have the lowest anxiety-like behavior and appear resilient to the anxiogenic effects of chronic stress. Low anxiety in Kv3.1 KOs has previously been reported in males (Parekh et al, 2018); these results replicate this observation in females. This study is the first to combine Kv3.1 deficiency with chronic stress.…”
Section: Discussionsupporting
confidence: 90%
“…The evidence for stress resilience in Kv3.1 KOs supports the hypothesis of overinhibition in stress-induced anxiety. Kv3.1 KO animals have decreased activity of fastspiking interneurons like PV cells and therefore reduced inhibitory signaling (Parekh et al, 2018). We hypothesize, therefore, that this genetic reduction in inhibitory neurotransmission prevents stress-induced over-inhibition and anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Numerous studies highlighted the growing number of hereditary or acquired diseases with which this channel is associated. Kv3.1 is involved in neurologic epilepsy [ 15 ] and neurodegenerative diseases such as multiple sclerosis [ 16 ] and Alzheimer’s [ 13 ], in cancer tumor hypoxia [ 17 ] and in behavior disorders such as bipolar disorder [ 18 ] and schizophrenia [ 19 ]. Kv3.1 dysfunction was also reported in cases of circadian cycle disturbance, sleep loss [ 20 , 21 ] and depression [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This modulation might be therefore a promising therapeutic tool in disorders associated with dysfunctions of inhibitory controls and unstable neuronal excitability, such as affective disorders. Recent pieces of evidence highlighted the potential role of this modulation in MDD and in BPAD, with preclinical studies that demonstrated that reduced K v 3 in PV-INs in the dentate gyrus induced depression phenotypes (Medrihan et al, 2020) and that K v 3.1and K v 3.2-positive modulators are able to reverse and prevent manic behaviors in mouse models (Parekh et al, 2018). For these reasons, K v 3.1-and K v 3.2-positive modulators are now being assessed in clinical trials and appear to be safe for human use (National Library of Medicine (U.S), 2019).…”
Section: Novel Pharmacological Approachesmentioning
confidence: 99%